Do texto à melodia das palavras na língua Ticuna - Felix, Nazareno Sampaio (2018)
The proposal of this thesis is to study the words of a tonal language, not in isolation, but inside texts where they acquire their real meanings/senses. This way, based on short narratives, this thesis presents some of the properties of the melodic patterns of words of the Ticuna language, spoken by the indigenous communities living in the High Solimões, in the state of Amazonas, Brazil. By focusing, mainly, on the melodic patterns of the words as they are employed in the texts , we consider that the understanding of the Ticuna people’s way of life, social organization and culture cannot be told apart from their histories. We have collected some of these histories , which were also transcribed and investigated by us, before focusing on the various words’ entries, together with their melodies and uses in sentences taken from them, and, when it is the case, presented in paradigms. Our main aims here are to contribute to the refinement of Ticuna’s dictionary ( cf. Soares 2000a, 2000b) , to the spread of the knowledge of a tonal language, and, besides that, to the teaching of Ticuna not only to the students ,but also to the young and elderly people. As the words of a language get their meanings/ senses in the texts where they are inserted , these texts collected and analyzed by us are also an important part of this thesis as well as of future practical teaching.